Fluoride-mediated dephosphonylation of α-diazo-β-carbonyl phosphonates - Phatake, Ravindra S.; Mullapudi, Venkanna Babu; Wakchaure, Vivek Chandrakant; Ramana, Chepuri V. (Organic Letters, 2016)
The possibility of fluoride-mediated selective dephosphonylation of α-diazo-β-carbonyl phosphonates such as the Ohira-Bestmann reagent has been proposed and executed. The resulting α-diazocarbonyl intermediates undergo a (3 + 2)-cycloaddition at room temperature with conjugated olefins and benzynes. Interestingly, under the current conditions, the resulting cycloaddition products underwent either N-acylation (with excess α-diazo-β-carbonyl phosphonates) or Michael addition (with conjugated olefins).